2013
DOI: 10.1111/liv.12173
|View full text |Cite
|
Sign up to set email alerts
|

LiverAtlas: a unique integrated knowledge database for systems‐level research of liver and hepatic disease

Abstract: LiverAtlas is the most comprehensive liver and hepatic disease resource, which helps biologists and clinicians to analyse their data at the systems level and will contribute much to the biomarker discovery and diagnostic performance enhancement for liver diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 35 publications
0
19
0
1
Order By: Relevance
“…We found that the differentially expressed transcripts and proteins screened in the HCC cell lines, which emphasized the metastatic versus nonmetastatic potentials, were different from those genes screened in liver carcinogenesis by proteome, which focused on the tumorous versus nontumorous tissues . Our results added useful information to the previously published LiverAtlas , including a total 627 metastasis‐relative genes listed in Supporting Information Table 2 and many newly identified genes such as IPO5 , SON , PITRM1 , PAICS , SF3B2 , FGFR1OP , SEC63 , MTO1 , PIAS4 , DDX49 , YTHDC2 , and MRPL57 shown in Supporting Information Table 2C of which 28 were overlapped genes between the 351 significant transcripts and 304 proteins.…”
Section: Resultsmentioning
confidence: 78%
“…We found that the differentially expressed transcripts and proteins screened in the HCC cell lines, which emphasized the metastatic versus nonmetastatic potentials, were different from those genes screened in liver carcinogenesis by proteome, which focused on the tumorous versus nontumorous tissues . Our results added useful information to the previously published LiverAtlas , including a total 627 metastasis‐relative genes listed in Supporting Information Table 2 and many newly identified genes such as IPO5 , SON , PITRM1 , PAICS , SF3B2 , FGFR1OP , SEC63 , MTO1 , PIAS4 , DDX49 , YTHDC2 , and MRPL57 shown in Supporting Information Table 2C of which 28 were overlapped genes between the 351 significant transcripts and 304 proteins.…”
Section: Resultsmentioning
confidence: 78%
“…28,29 With the accumulation of proteome data sets generated from different tissues and cell lines, to date, 50−60% of protein-coding genes have been identified at the proteome level. 3,35 However, because of limitations associated with the detection sensitivity and dynamic range of available mass spectrometers, data saturation could be easily reached.…”
Section: Approaching the Sample Number-independent Data Saturation Stmentioning
confidence: 99%
“…Liver diseases are imported from DO [1], and UMLS [39]. These liver diseases are organized by Human Liver Disease Ontology (HuLDO) developed by ourselves [40]. HuLDO is a standardized method to classify and annotate human liver diseases.…”
Section: Construction and Contentmentioning
confidence: 99%
“…HuLDO is a standardized method to classify and annotate human liver diseases. It is a comprehensive lexicon which contains detailed information on hepatic disease and demonstrates the logical and medical relationships between different diseases [40]. To assess the quality of each entry, we use a semi-quantitative method which considers the reliability and the number of data sources.…”
Section: Construction and Contentmentioning
confidence: 99%